FAKTOR-FAKTOR YANG MEMPENGARUHI PASANGAN USIA SUBUR (PUS) DALAM MEMILIH KONTRASEPSI IMPLANT DI PUSKESMAS SEI LANGKAI - Purba, Rolin; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
A contraceptive implant is a long-term medical device implanted superficially in a woman’s upper arm used for the purpose of birth control. It is a contraceptive method that is provably practical and effective with only 1 out 100 women using it proven unsuccessful which means the abortiveness rate is very low, only 0.05%. However, the data of Puskesmas Sei Langkai in Sagulung District, Batam, in 2018, indicated that the use of contraceptive implant is significantly less popular than other type of birth control methods where the total of active acceptors of contraceptive implant is making up only 9.36%. This research aims to discover the factors influencing the decision in choosing contraceptive implant amongst fertile age couples in Puskesmas Sei Langkai, Batam; Another objective is to know distributive frequency and correlation between knowledge, behavior, role of health workers, and husband support on choosing contraceptive implant. The research is quantitative employing analytical survey method with cross-sectional approach. The sample population is 33 acceptors, out of 994 contraceptive acceptors in total, using simple random sampling. The data collecting technique uses questionnaire form. Analytical methods used univariate, and bivariate analysis. The result of univariate analysis from four factors indicates the knowledge on the implant is considered estimable, behavior on the implant is met with positive response, but the role of health workers in promoting the use of the implant is notably low, and the husband response in choosing the implant is negative, lacking in support The result of bivariate analysis with Fisher test confirms a significant correlation between knowledge factor (p=0,002), behavior factor (p=0,004) the role of health workers (p=0,001), and husband support (p=0,000). In suggestion, with vast range of benefits, health workers are expected to promote contraceptive implant so the general public can have different option in choosing contraception